Analisis Perkembangan Umkm Sektor Informal Kota Blitar Akibat Dampak Pandemi Covid-19 - Fatimatul Nikmah (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This research is entitled "Analysis of the Development of MSMEs in the Informal Sector of Blitar City Due to the Impact of the Covid-19 Pandemic". The impact of the COVID-19 pandemic in Blitar City caused the informal sector business to experience a decline in turnover due to a decrease in sales. Some of the informal sectors, especially those based on food and beverages, were disrupted due to delays in the distribution of raw materials and decreased production capacity due to the implementation of restrictions on community activities (PPKM) in the city of Blitar. The purpose of this study is to analyze the development of MSMEs in the informal sector of Blitar City due to the impact of the covid-19 pandemic, to determine the extent to which business actors persist in financial and capital problems in the informal business sector of Blitar City due to the impact of the covid-19 pandemic and to determine the influence and effectiveness of government policies. for the micro and informal business sectors that have been carried out during the Covid-19 pandemic. The method used in this study is a qualitative method using the mills and hubberman methods. Based on the results of the study, it shows that the condition of the informal sector business in the city of Blitar in 2020 experienced a temporary cessation of operations and those that were still surviving experienced a decline in turnover. Meanwhile, in 2021 it was found that there were a small number of informal sector businesses that stopped permanently, but for informal sector businesses that were still surviving, there was an increase in turnover. Furthermore, related to capital assistance from the government in the form of BPUM, direct assistance and KUR have not been evenly received by business actors in the informal sector, so that on average they still survive using their own capital. Finally, it can be said that during the COVID-19 pandemic, informal sector businesses were not significantly affected.